Robust output feedback control for dynamic positioning of turret-moored vessels based on bio-inspired state observer and online constructive fuzzy system - Yulong Tuo; Shasha Wang; Chen Guo; Shuang Gao (International Journal of Naval Architecture and Ocean Engineering, 2022)
This paper investigates the dynamic positioning control of turret-moored vessels with uncertainties, unknown disturbances and velocities. Firstly, a bio-inspired state observer is proposed based on the bio-inspired neural dynamics model to estimate unknown velocities without vessel dynamics model. Meanwhile, an online constructive fuzzy approximator is designed to approximate uncertainties and unknown disturbances. To ensure fuzzy rules adequate and parsimonious, an online constructive scheme is proposed to adjust the fuzzy system structure without any prior knowledge. Based on the designed state observer and fuzzy approximator, a reliability-based robust output-feedback controller is proposed to make the reliability and heading converge to desired values. A reliability-based matrix is applied into the adaptive fuzzy parameter update law to simplify the stability analysis of closed-loop control system. The convergence of reliability can ensure full utilization of mooring system to maintain the vessel within allowable region. Finally, simulations and comparisons show the performance of proposed methods.